The Effect of Regional Original Revenue (PAD), Budget Financing Surplus (SILPA), Regional Wealth on Capital Expenditure with Economic Growth as a Moderating Variable in Central Java Province for the 2019-2021 Period - M.Dwiky Ariyanto; Ngurah Panji Mertha Agung Durya; Amina Intes; Uwe Barroso; Kruger Margarida (Yayasan Adra Karima Hubbi, 2024)
This study aims to determine the effect of Regional Original Income (PAD), Excess Budget Financing (SILPA) and Regional Wealth on Capital Expenditures with economic growth as a moderating variable. This research was conducted in Central Java Province as many as 35 regencies/cities consisting of 29 regencies and 6 cities. This study uses budget realization report data obtained from the DGT website. The analytical method used to test the hypothesis in this study is Moderated Regression Analysis (MRA). The results of this study indicate that economic growth does not moderate the effect of regional original income on capital expenditure, but economic growth is able to moderate excess budget financing and regional wealth on capital expenditure.